ANALISA LUMPUR PEMBORAN TERHADAP SWELLING CLAY PADA SUMUR “X” LAPANGAN “AFFIKAH” - Diba, Affikah Fara; Mukmin, M Nur; Afifah, Rohima Sera (Sekolah Tinggi Teknologi MIGAS, 2019)
In drilling operations, mud planning is one of the most important factors in supporting the success of drilling operations in oil wells. Planning for the use of drilling mud is used for maximum results in cutting and maintaining drilling wells. This study aims to determine the cause of swelling and what problems will be caused if swelling control is carried out less than optimally. In this study, we analyze the mud that will be used in drilling operations, so that it can prevent or minimize swelling of clay in the shale system by adjusting the polyamine content to be used. After doing the research, it was found that at the